Cultivating Social Character through Project-Based Learning in Islamic Elementary Schools in Semarang - Imron, Ali; Muarifah, Siti; Oktradiksa, Ahwy; Romdhoni, Ali (Universitas Muhammadiyah Magelang, 2024)
By Project Based Learning, students of Elementary School in Semarang can develop their social-caring character. In this digital era, helpful character, tolerance, social act, and good morality are declining. This research assesses if project-based learning instills those characters in the students. This qualitative research used NVivo software to analyze interviews, observation, document analyses, and Focus Group Discussions. Principles, instructors, and students from various elementary schools in Semarang which apply project-based learning participated in the research. Morning alms, visits to orphanages, donations on Fridays, anti-bullying socialization, and incidental activities such as sharing takjil and social fundraising varied in each initiative. Those projects enable students to use their talents in real-life situation. Project based learning develops social skill of students although the plan and the implementation are difficult. Students' social awareness, teamwork, and empathy increase significantly. Project based learning has been proven can significantly help elementary school students improve their social-caring character so that it gives valuable contribution to character education and becomes model for other schools.